Analisis Risiko Kesehatan Lingkungan Kandungan Besi Dan Mangan Pada Air Sumur Bor Di Desa Polewali (Window of Public Health Journal, 2025)
Groundwater is the primary source widely used by people in Indonesia, as it is relatively easy to access and considered cleaner. The purpose of this study is to determine the environmental health risks associated with the Fe and Mn content in the drilled well water consumed by the community in Polewali Village, South Baebunta District, North Luwu Regency. This study employs a descriptive observational design with an Environmental Health Risk Analysis (EHR) approach. The results show that of the 30 communities exposed to Fe, three communities have RQ > 1 and 27 communities have RQ ≤ 1, while all 30 communities exposed to Mn have RQ values ≤ 1. Based on these data, it is known that three people exposed to Fe have a risk level that exceeds the safe limit, while 30 communities exposed to Mn are still below the risk level or are not at risk at this time, pending the next few years. Recommendations based on the results of this study suggest that remediation and treatment of drilled well water should be carried out.